Exploring current practices and governance of Malaysian mosque committees in managing the mutual benevolent of Khairat death fund - Jaaffar, Mohd Yassir; Syed Ibrahim, Sharifah Norhafiza; Mahmud, Radziah; Bani, Hamidah; Mustafa, Mohd Ariff; Ali, Kamariah; Syed Alwi, Sharifah Faigah (2023)
This study intends to gauge the different practices and management governing the mutual benevolent Khairat death fund in Malaysia. A series of interviews were conducted with the representatives from the State Islamic Religious Council (SIRC) and the Mutual Benevolent Death Fund committees in the rural areas of three different states. This qualitative study employed thematic analysis to analyze the different practices and management of this death fund. Results show there are three different forms of governance practices of this Khairat death fund namely: (i) management and governance under a committee registered under the Register of Society (ROS); (ii) management and governance under a mosque committee registered under ROS; and (iii) administration exclusively under a mosque committee. Findings from this research are applicable to the sampled rural areas only. This study suggests that all relevant players, such as the ROS, Khairat Society, mosque management, and SIRC should actively contribute to addressing the issue to safeguard the rights and interests of Khairat members and ensure the long-term viability and sustainability of the fund. Provide empirical evidence the presence of separate governance frameworks for the management and supervision of the Khairat death fund.